The Impact on Geographic Location Accuracy due to Different Satellite Orbit Ephemerides - Celestino, Claudia C.; Sousa, Cristina T. [UNESP]; Yamaguti, Wilson; Kuga, Helio Koiti (Hindawi Publishing Corporation, 2009)
The current Brazilian System of Environmental Data Collection is composed of several satellites (SCD-1 and 2, CBERS-2 and 2B), Data Collection Platforms (DCPs) spread mostly over the Brazilian territory, and ground reception stations located in Cuiaba and Alcantara. An essential functionality offered to the users is the geographic location of these DCPs. The location is computed by the in-house developed GEOLOC program which processes the onboard measured Doppler shifts suffered by the signal transmitted by the DCPs. These data are relayed and stored on ground when the satellite passes over the receiving stations. Another important input data to GEOLOC are the orbit ephemeris of the satellite corresponding to the Doppler data. In this work, the impact on the geographic location accuracy when using orbit ephemeris which can be obtained through several sources is assessed. First, this evaluation is performed by computer simulation of the Doppler data, corresponding to real existing satellite passes. Then real Doppler data are used to assess the performance of the location system. The results indicate that the use of precise ephemeris can improve the performance of GEOLOC by reducing the location errors, and such conclusion can then be extended to similar location systems. Copyright (C) 2009 Claudia C. Celestino et al.